(untitled) (Bangladesh Journal of Medical Science, 2012)
During routine dissection of an old male cadaver, in the Department of Anatomy, Pinnamaneni Siddhartha Institute of Medical science, Chinoutpalli, Andhra Pradesh, India, presence of right superior aberrant renal artery was noted. It took origin from the lateral aspect of abdominal aorta, below the origin of superior mesenteric artery and above the right main renal artery .The right superior renal artery run towards upper pole of the right kidney. Proper knowledge of variations of the arteries supplying the kidney is essential not only to the anatomists but also to the vascular surgeons, urologists, nephrologists and radiologists. Such vascular variations as noted in the present study have been explained in light of embryogenic development. DOI: http://dx.doi.org/10.3329/bjms.v11i2.11484 Bangladesh Journal of Medical Science Vol. 11 No. 02 April 2012: 148-150